AgentPlanner - agent-based timetabling system - Tkaczyk, Rafal; Ganzha, Maria; Paprzycki, Marcin (Informatica, 2016)
The aim of the paper is to describe the AgentPlanner, an agent-based timetabling system. After its initial implementation (described in [1]), based on results of experiments, we have modied the design (to eliminate discovered shortcomings). Here, we describe the improved AgentPlanner and compare its performance with the, state-of-the-art Free Timetabling Software (FET).